21.9k views
4 votes
30.52

Rhett is solving the quadratic equation 0= x2 – 2x - 3 using the quadratic formula. Which shows the correct substitution of the
values a, b, and c into the quadratic formula?​

1 Answer

3 votes

Answer:

a = 1; b = - 2; c = - 3

Step-by-step explanation:

Given the quadratic equation:

x^2 - 2x - 3 = 0

The quadratic formular goes thus :

[-b ± √(b^2 - 4ac)] / 2a

From the general form of a quadratic equation:

Ax^2 + Bx + c = 0

Comparing the given quadratic equation with the formula:

Coefficient of x^2 = a = 1

Coefficient of x = b = -2

Constant c = -3

[-(-2) ± √((-2)^2 - 4(1)(-3)] / 2(1)

[2 ± √4 - (-12)] / 2

[2 ± √4 + 12] / 2

[2 ± √16] / 2

[2 ± 4] / 2

(2+4)/2 or (2-4)/2

6/2 or - 2/2

3 or - 1

User Ilena
by
4.6k points